2018
DOI: 10.1080/09603123.2018.1429580
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Legionella pneumophila on glass and plumbing materials commonly used in domestic water systems

Abstract: We aimed to investigate the adhesion of Legionella pneumophila serogroup1 and L. pneumophila serogroup2-15 on glass, galvanized steel, stainless steel, copper, Polyvinyl chloride(PVC), Cross-linked polyethylene(PEX-c) and Polypropylene Random Copolymer(PPR). The surface physicochemical properties of both bacterial cells and materials were estimated through contact angle measurements. The roughness and surface topography of the materials were evaluated by Atomic Force Microscopy. The two L. pneumophila serogrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Several studies have reported that the growth and the proliferation of L. pneumophila are influenced by many factors, such as pipe materials, temperature, stagnation, flow circumstances, corrosion, and pipe roughness (Assaidi et al 2018a(Assaidi et al , 2018b. In our study, the aggravating effect of the pipe materials on colonization was also confirmed.…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have reported that the growth and the proliferation of L. pneumophila are influenced by many factors, such as pipe materials, temperature, stagnation, flow circumstances, corrosion, and pipe roughness (Assaidi et al 2018a(Assaidi et al , 2018b. In our study, the aggravating effect of the pipe materials on colonization was also confirmed.…”
Section: Discussionsupporting
confidence: 82%
“…According to the literature, the hydrophobicity of a bacterial cell is largely influenced by the residues and structures on the cell surfaces, which can be hydrophilic or hydrophobic [ 10 , 19 , 37 ]. Hence, bacterial hydrophobicity varies among species and strains, even within the same strain, depending on the mode and stage of growth, growth medium composition, and even the analysis technique [ 7 , 9 , 38 , 39 ], potentially explaining the variation of hydrophilicities even within the same species in our work.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence governs the ability of bacteria to colonize different surfaces. For this reason, the limitation of adhesion process is favorable and highly encouraged in the course of the creation of novel biomaterials, both for external use and implanted, as well as the development of anti-infectious therapeutics or production of improved materials for industrial purposes [ 30 , 44 , 102 ]. The capability of AFM to measure adhesion forces between the catilever tip and scanned sample is particularly useful in this manner.…”
Section: Afm-based Investigation As a Novel Approach To Fight Withmentioning
confidence: 99%
“…However, studies have shown that after a long period of time there is no difference between copper and plastic materials [ 127 , 128 ]. In another study, Assaidi et al tested the adhesion changes of Legionella pneumophila serogroup 1 and serogroup 2 to different materials used in water systems [ 102 ].…”
Section: Afm-based Investigation As a Novel Approach To Fight Withmentioning
confidence: 99%